Effect Of Different Yeast Extract Concentration In Membrane-Less Microbial Fuel Cell (ML-MFC) For Electricity Generation Using Food Waste As Substrate - Mohammad Faizal, Mohammad Mirza (Universiti Sains Malaysia, 2020)
Electricity is the basic energy in our daily life and there are about 14 % of global population that did not get the access to electricity. Furthermore, 45 % of the main composition of waste that produced daily is food waste. As a result, microbial fuel cell (MFC) become the solution as it has the potential for food waste treatment and electricity power generation. This study is being conducted to utilize the food waste that collected from E-Idaman, Kedah, to generate energy while focusing the effect of different yeast extract level in a membrane-less microbial fuel cell (ML-MFC)